Fatal drowning among tourists and recently arrived individuals from overseas at South Australian Metropolitan beaches. Issue 5 (3rd September 2021) - Stephenson, Lilli; Byard, Roger W.; van den Heuvel, Corinna; Peden, Amy E.
ABSTRACT: As 17% of all drownings occur at beaches, a study of unintentional fatal drownings at South Australian (SA) metropolitan beaches was undertaken, specifically evaluating the risk for individuals born overseas. All cases of fatal unintentional drowning between July 2002-June2018 at SA beaches were sourced from the Royal Life Saving National Fatal Drowning Database. Demographics and causal factors were analysed for all SA drownings and specifically for those at metropolitan beaches amongst those known to be born overseas. Fifty-seven drowning deaths at SA beaches were identified. Of the 54% (n=31) of beach drownings which occurred at metropolitan beaches, 36% (n=11) of decedents were overseas-born. Risks were highest for individuals from Burundi and lowest for those from the United Kingdom. Drowning deaths at SA metropolitan beaches among overseas-born most commonly involved children who were swimming or merely playing at the water's edge, in summer and during afternoons. With increasing tourism forensic pathologists will encounter greater numbers of individuals from overseas who have drowned. This means that specific and different cultural processes and attitudes to medicolegal investigations will be encountered. Preventive efforts aimed at reducing beach drowningamong at-risk groups should also includeculturally-appropriate campaigns.